IMPROVING STUDENTS’ ABILITY IN READING COMPREHENSION TEST BY USING SCANNING - Hermida, Rita (STKIP An-Nur, 2018)
ABSTRACTReading is one four major skills in English besides speaking, listening and writing. Most of students who are still poor in English often find difficulties in doing reading comprehension test. Using Scanning technique can improve their ability in it. The aims of using scanning in reading comprehension test are to solve the above problem and to see the effectiveness of it. The subject of the research was the sixth semester students, and the sample taken randomly. To do the research, the writer tried to find data by teaching them about reading comprehension and focusing on scanning. The writer also gave them pre-test and post test and interviewed them informally. After collecting data, the writer analyzed the score of pre-test and post-test. From the result of analysis, it was found that the average scores are 71,35 for pre-test and 87,70 for post-test. It indicates that the application of scanning in reading comprehension test can improve students’ ability as well as motivate them in learning English. KEY WORDS: scanning, and reading comprehension test.